Arithmetic in General Education. National Council of Teachers of Mathematics, Yearbook 16 [1941] - National Council of Teachers of Mathematics, Inc., Reston, VA.; Reeve, W. D.; National Council of Teachers of Mathematics, Inc., Reston, VA. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1941)
This yearbook is the final report of the National Council Committee on Arithmetic. Having endorsed the "meaning theory" of arithmetic instruction, an attempt is made to develop a position that might serve as a basis for improvement of the arithmetic program. After a chapter on the function of subject matter in relation to personality and one on curriculum problems, there follows a chapter on each of the early grades, middle grades, and high school. The next two chapters present discussions of the social phase of arithmetic instruction and enrichment activities, respectively. Chapter 9 presents a discussion of the present status of drill, followed by a chapter on evaluation. New trends in learning theory are applied to arithmetic in chapter 11. Chapter 12 poses many questions for introspective examination. The yearbook concludes with a chapter on interpretation of research followed by listings of 100 selected studies and 100 selected references. (LS)
Keywords: Arithmetic; Curriculum; Curriculum Problems; Elementary School Mathematics; Enrichment Activities; Evaluation; Learning Theories; Mathematics Education; Reference Materials; Reports; Research Reviews (Publications); Yearbooks; Reports, Descriptive